1999
DOI: 10.1207/s15327914nc330205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Administration of Tea, Decaffeinated Tea, and Caffeine on the Formation and Growth of Tumors in High-Risk SKH-1 Mice Previously Treated With Ultraviolet B Light

Abstract: Treatment of SKH-1 mice with ultraviolet B light (UV-B, 30 mJ/cm2) twice a week for 22-23 weeks resulted in tumor-free animals with a high risk of developing malignant and nonmalignant tumors during the next several months in the absence of further UV-B treatment (high-risk mice). In three separate experiments, oral administration of green tea or black tea (4-6 mg tea solids/ml) as the sole source of drinking fluid for 18-23 weeks to these high-risk mice inhibited the formation and decreased the size of nonmal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 13 publications
0
77
1
1
Order By: Relevance
“…The regular teas were more effective inhibitors of carcinogenesis than the decaffeinated teas, and adding back caffeine to the decaffeinated teas restored their inhibitory activities (3,4). These results indicated that caffeine is a major component of tea responsible for its inhibitory effect on UVB-induced tumor formation in mice.…”
Section: Introductionmentioning
confidence: 83%
“…The regular teas were more effective inhibitors of carcinogenesis than the decaffeinated teas, and adding back caffeine to the decaffeinated teas restored their inhibitory activities (3,4). These results indicated that caffeine is a major component of tea responsible for its inhibitory effect on UVB-induced tumor formation in mice.…”
Section: Introductionmentioning
confidence: 83%
“…Studies from our laboratory showed that administration of caffeine or caffeine sodium benzoate has sunscreen activity, increases the elimination of DNA-damaged cells by apoptosis, and inhibits UVB-induced carcinogenesis in SKH-1 mice (3,4,7,8,27,42). Topical applications of caffeine or caffeine sodium benzoate to UVBpretreated high-risk mice inhibited carcinogenesis in the absence of further UVB treatment (4,27,42), and administration of caffeine also enhanced apoptosis in the tumors (42). The results of these studies suggest that caffeine and caffeine sodium benzoate may be mechanistically novel agents for inhibiting sunlight-induced skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…administration of green or black tea on the formation of UVBinduced keratoacanthomas and squamous cell carcinomas in SKH-1 hairless mice (1,2). The regular teas were more effective than the decaffeinated teas, adding back caffeine to the decaffeinated teas restored their inhibitory activities, and administration of caffeine alone strongly inhibited tumor formation (3,4). These results indicated that caffeine is a major component of tea responsible for its inhibitory effect on UVB-induced tumor formation in mice.…”
Section: Introductionmentioning
confidence: 95%
“…Conney et al [35][36][37] demonstrated inhibitory effects of orally administered tea, decaffeinated tea, and caffeine against UVB-induced skin tumorigenesis in mice and a close association between inhibition of carcinogenesis and reduction of adipose tissue by tea and caffeine [35]. Decaffeinated green tea or decaffeinated black tea was found to be much less effective in inhibiting the tumor formation and reducing fat levels, and adding caffeine to the decaffeinated green or black tea restored the inhibitory effects.…”
Section: Skin Carcinogenesismentioning
confidence: 99%